Pharmacological inhibition of endoplasmic reticulum stress mitigates testicular pathology in a mouse model of simulated microgravity. (March 2023) - Ranade, Anu V.; Khan, Amir Ali; Gul, Muhammad Tehsil; Jose, Josemin; Ramachandran, Gopika; Qaisar, Rizwan; Karim, Asima; Ahmad, Firdos; Abdel-Rahman, Wael M.
Abstract: Background: Simulated microgravity during hindlimb unloaded (HU) induces multi-organ pathologies in mice, including testicular dysfunction. However, a detailed characterization of testicular histology and its driving molecular mechanisms remains elusive. We investigated the potential contribution of elevated endoplasmic reticulum (ER) stress to testicular atrophy in HU mice. Methods: We divided male c57BL/6j mice into a control group (C) or unloaded mice without treatment (U), or treated with 4PBA (UP), an ER stress inhibitor, for three weeks. At the end of the experiment, mice were euthanized, and testes tissues were dissected for histopathology and mRNA sequencing. Results: HU was associated with significant testicular atrophy (p = 0.03) and several histopathological alterations, including a reduction in the diameter of seminiferous tubules (p < 0.001), epithelial thinning (p < 0.001), reduced sperm density (p < 0.001), and thickening of the epididymal epithelium (p < 0.001). mRNA sequencing revealed alterations in several pathways associated with oxidative stress, protein catabolism, and inflammation induction (all p < 0.05). Three weeks of treatment with 4PBA prevented testicular atrophy (p = 0.214), partly restored testicular microarchitecture, and reversed changes in the transcriptomic profiling of HU mice. Conclusion: Our novel findings indicate a mechanistic role of elevated ER stress in causing testicular pathology during HU conditions. Based on findings, we report a therapeutic potential of 4PBA in reversing testicular pathology in conditions mimicking prolonged bed rest and spaceflight. Graphical abstract: Image 1 Highlights: Hindlimb unloaded (HU) mice exhibit testicular disruption in histology. Testes of HU mice also show elevated endoplasmic reticulum (ER) stress. Pharmacological inhibition of ER stress reverses testicular histology during HU. Signature transcriptomic changes accompany ER stress-induce testicular disruption. Inhibiting ER stress may be a molecular target to restore testes during HU.